Pengaruh suasana lingkungan toko terhadap keputusan pembelian konsumen pada Toko Reni Jaya Cabang Majalengka - Mugni, Mumu; Yaya Sunjaya (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This research aims to collect data and information about the influence of the store environment on consumer purchasing decisions at the Reni Jaya Store, Majalengka Branch. Then the data obtained will be poured in the form of writing a thesis as one of the requirements in obtaining a Bachelor of Management degree. The research method used is descriptive and verification methods. The population in this study is all consumers of the Reni Jaya Store, Majalengka Branch, Majalengka Regency, which is not known for sure. The sample obtained was 96 respondents using a sampling technique, namely probability sampling with simple random sampling. The instrument used is a questionnaire. The variables used in this study consisted of independent variables and dependent variables. The independent variable is the Atmosphere of the store environment. In contrast, the dependent variable is the purchase decision variable (Y). Hypothesis testing was analyzed using simple linear regression, correlation coefficient analysis, determination, and t-test. The results of hypothesis testing indicate that the environmental Atmosphere (X) influences the Purchase Decision (Y). This can be seen from the value of tcount (12.2991), which is greater than the value of ttable (1.66123). The environmental Atmosphere (X) has an influence of 61.67% on the purchasing decision variable (Y), and the remaining 38.33% is influenced by other variables outside of this study. The correlation coefficient value of 0.7853 indicates a strong relationship between environmental conditions and purchasing decisions at the Reni Jaya Store, Majalengka Branch, Majalengka Regency. The regression model is as follows: Y = 1.72 + 0.46X. The constant value means that when X is 0, then Y is 1.72. In contrast, the regression coefficient b means that in every positive environmental Atmosphere (X), the purchase decision (Y) will increase by 0.46 units.